Concentrations of Aerial Pollutant Gases in Selected Poultry Pens in Imo State, Nigeria - Okoli, I.C.; Alaehie, D.A.; Akanno, E.C; Okoli, C.G.; Opara, M.N.; Uchegbu, M.C.; Ogundu, U.E.; Iheukwumer, F.C. (International Journal of Poultry Science, 2004)
Research on the concentrations of pollutant gasses in tropical livestock buildings is needed in order to establish baselines for exposure limits in the context of animal and human welfare in tropical environments. Concentrations of aerial ammonia NH4, nitrous oxide (NO2), flammable gas (methane, CH4), carbon monoxide (CO), hydrogen sulfide (H2S) and sulfur dioxide (SO2) were measured in five intensive layer farms located Imo state during the month of August 2002. Data obtained were correlated with poultry house measurements in other to understand rates of increases of these pollutants as a result of changes in poultry house measurements. Overall mean aerial concentration of CO (3.11±0.73 ppm) was highest, followed by the 1.93 ± 0.14 ppm and 1.53 ± 0.71 ppm recorded for CH4 and H2S respectively, while the 0.09 ± 0.19 ppm and the 0.14 ± 0.20 recorded for SO2 and NH4 respectively were lowest. The range of 3.25 ± 0.7ppm to 4.0±0.0 ppm of CO obtained in the four pens FA, FB1, FB2 and FC was significantly (P